Discovering sexual health conversations between youth and youth development professionals - Gupta, N.; Chandak, A.; Gilson, G.; Kneip Pelster, A.; Goldsworthy, R.; Baldwin, K.; Fortenberry, J.; Fisher, Christopher (2015)
Youth development professionals (YDPs) working at community-based organizations are in a unique position to interact with the adolescents because they are neither parents/guardians nor teachers. The objectives of this study were to explore qualitatively what sexual health issues adolescents discuss with YDPs and to describe those issues using the framework of the Sexuality Information and Education Council of the United States (SIECUS) comprehensive sexuality education guidelines. YDPs reported conversations with adolescents that included topics related to the SIECUS key concepts of human development, relationships, personal skills, sexual behavior, and sexual health.